Self/scape: an exploration of belonging and wayfaring - Paredes, Miguel Angel (Department of Drama, 2020)
Self/Scape is an autoethnographic sonic exploration of searching, belonging, and praying through sound as well as exploring the socio-cultural conditions and the lived experiences of a globalized Latino. Following the framework of Practice as Research (PaR), Miguel has been creating and theorizing about and through this piece during his two-year degree. This piece is the culmination of Miguel’s research at UCT in which a theatrical production is transformed into a curated space that is made to coexist with(in) a digital soundscape. That is to say that this piece has been created to be experienced through the use of headphones and QR codes. Each QR code will be specifically placed in relation to the content of the code which documents the journey of self-discovery through a multitude of spaces around the world from Los Angeles to Cape Town.